Unraveling the cGAS/STING signaling mechanism: impact on glycerolipid metabolism and diseases - Su, Jie; Cheng, Fuyu; Yuan, Wei (Frontiers in Medicine, 2024)
The cyclic GMP-AMP synthase (cGAS) and its downstream effector, the stimulator of interferon genes (STING), are crucial components of the innate immune response, traditionally recognized for their role in detecting cytosolic DNA from pathogens and damaged host cells. However, recent research indicates that the cGAS-STING pathway also significantly impacts metabolic processes, particularly glycerolipid metabolism. Glycerolipids are essential for energy storage and cellular membrane integrity, and their dysregulation is linked to metabolic disorders such as obesity, insulin resistance, and non-alcoholic fatty liver disease (NAFLD). Both cGAS and STING are expressed in various metabolic tissues, suggesting a potential role in lipid homeostasis. Chronic activation of the cGAS-STING pathway may promote inflammatory states that exacerbate insulin resistance and lipid accumulation, forming a feedback loop of metabolic dysfunction. This review explores the emerging relationship between cGAS/STING signaling and glycerolipid metabolism, discussing the mechanisms through which this pathway influences lipid regulation and the potential for therapeutic interventions. By integrating insights from immunology and metabolism, we aim to provide a comprehensive understanding of how the cGAS-STING axis may serve as a novel target for addressing metabolic disorders and enhancing metabolic health outcomes.